Work of Teacher with Parents in Conditions of Inclusive Education - V. V. Khitryuk; M. G. Sergeyeva; N. L. Sokolova (Научный диалог)
The research urgency is caused by heterogeneity and polysubjectness ща inclusive educational space that form “the other” relationship between the parties in quality and vector direction. Special attention is given to identifying and testing new forms and technologies of interaction of the teacher with students’ parents. Issues of professional competence of teachers of the first stage of general secondary education (primary school) are covered. It is shown that the competence of teachers in inclusive education, acceptance of its meanings, values, conditions; their willingness to include children with different educational abilities, needs, opportunities in communication, interaction, educational process; ensuring the psychological comfort of all its members (and especially children and their parents) are the determining factors of inclusive education quality. The results of experimental activities (2015-2017) are presented, the aim of which was to identify the effectiveness of training in working with parents of students of primary school in the formation of inclusive educational space. The authors focus on the approval of the content of the complex thematic trainings during the pilot activities. The novelty of the research is seen in the fact that the new conditions for the development of inclusive preparedness of the teacher were identified and experimentally tested, the directions of qualitative renewal of the system of teacher’s work with parents were specified.